Seasonal dynamics of fungal communities in a temperate oak forest soil - Voříšková, Jana; Brabcová, Vendula; Cajthaml, Tomáš; Baldrian, Petr (The New phytologist, 2014)
Fungi are the agents primarily responsible for the transformation of plant-derived carbon in terrestrial ecosystems. However, little is known of their responses to the seasonal changes in resource availability in deciduous forests, including photosynthate allocation below ground and seasonal inputs of fresh litter. Vertical stratification of and seasonal changes in fungal abundance, activity and community composition were investigated in the litter, organic and upper mineral soils of a temperate Quercus petraea forest using ergosterol and extracellular enzyme assays and amplicon 454-pyrosequencing of the rDNA-ITS region. Fungal activity, biomass and diversity decreased substantially with soil depth. The highest enzyme activities were detected in winter, especially in litter, where these activities were followed by a peak in fungal biomass during spring. The litter community exhibited more profound seasonal changes than did the community in the deeper horizons. In the litter, saprotrophic genera reached their seasonal maxima in autumn, but summer typically saw the highest abundance of ectomycorrhizal taxa. Although the composition of the litter community changes over the course of the year, the mineral soil shows changes in biomass. The fungal community is affected by season. Litter decomposition and phytosynthate allocation represent important factors contributing to the observed variations.
Keywords: biodiverzita; Seasons; seasonality; temperate forests; houby; litter; Biomass; fungal community; koloběh uhlíku; roční období; dub (rod); půdní mikrobiologie; stromy; Quercus; Fungi; Biodiversity; Soil Microbiology; ekosystém; Ecosystem; ectomycorrhizal (ECM) fungi; Soil; půda; Trees; biomasa; forest soil; Carbon Cycle